P69 Do Patients Progress Whilst Undergoing Diagnosis and Staging For Lung Cancer: A Retrospective Audit?. (19th November 2012) - Kwong, R; Bradshaw, C; Finney, L; Burkill, GJ; Doffman, SR
Abstract : Background: In the last 10 years, the survival rate in lung cancer in the UK has improved, but remains lower than some counterpart European countries. The cancer waiting time initiative aimed to speed up the process from presentation to treatment to improve outcomes. All tumour sites follow a similar process with no distinction by tumour site. There is no published UK data on whether patients with lung cancer progress either symptomatically or by imaging whilst undergoing the diagnostic pathway. Methods: Two medical students at a University teaching hospital audited records of patients first seen in 2010 with lung cancer. Data regarding history, stage, histological diagnosis and performance status (PS) recorded at MDT were collected. In addition the recommended treatment plan from the MDT and the final treatment delivered were extracted from the Somerset Cancer Register (SCR) and case records. Only patients with non-small cell (NSCLC) or small cell (SCLC) lung cancer who underwent active anti-cancer treatment were included (n=70). A subgroup of 45 patients with CT scans at diagnosis and prior to treatment commencement were identified for radiological analysis of progressive disease (PD) defined by a change in TNM staging or growth on RECIST 1.1 criteria. All data was analysed using SPSS software (non-parametric Wilcoxon's/Chi squared tests). Results: Baseline characteristics are below. Median referral-to-treatment interval was 72 days (range 0–281). The interval between diagnosis and treatment varied dependent on stage and symptoms at presentation. 13 patients experienced a decline in PS (p=0.012). 8 patients (17.4%) had radiological PD; of those, 2 patients stage migrated. There was a positive association between PD and deterioration in PS (p=0.015), late stage disease at presentation (p=0.037) and poor PS at presentation (p=0.024). Late-stage disease (p=0.003) and presence of radiological PD (p=0.005) were associated with shortened survival. No patients with PD had a change in treatment. Conclusions: Patients with advanced lung cancer and poorer PS at presentation tend to progress rapidly. Further work should be carried out to determine predictive characteristics of those patients likely to progress whilst undergoing diagnostic work-up to ensure appropriate stratification. The majority of these patients had improved right ventricular function post thrombolysis. This small cohort study demonstrates the variability in the clinical presentations and physiological manifestations of massive PE, hence the need for early specialist input. The algorithm is an effective tool in identifying high mortality risk patients and those likely to develop pulmonary hypertension, thus allowing early specialist review and intervention.